The Implementing Geological Disposal Technology Platform – addressing the needs of new Member States. (2nd January 2018) - Kowe, R.; Delay, J.; Hammarström, M.; Beattie, T.; Palmu, M.
Abstract: The Implementing Geological Disposal of Radioactive Waste Technology Platform (IGD-TP) was launched in November 2009 to facilitate international cooperation in common areas of research, development and demonstration (RD&D) with a view to advancing the implementation of geological disposal facilities for spent fuel, high-level and other long-lived waste in Europe. The IGD-TP's Vision is that "by 2025, the first geological disposal facilities for spent fuel, high-level waste and other long-lived radioactive waste will be operating safely in Europe". Aside from most European waste management organisations, the IGD-TP currently has 124 members covering most of the RD&D actors in the field of implementing geological disposal of radioactive waste in Europe. Five years after its inception, the IGD-TP has been shown to play a leading role in coordinating joint actions for RD&D in radioactive waste geological disposal programmes. The work of the platform takes into account differences between the timing and challenges for the respective waste management programmes. Following implementation of Posiva's geological disposal facility in Finland it is expected that within the next 5 years the construction of the Swedish and French geological disposal facilities will commence. Within IGD-TP, the SecIGD2 project whose remit is "Coordination and Support Action under the 7 th Framework programme" aims at supporting, at the European level, the networking and structuring of RD&D programmes and competences in countries with less advanced geological disposal programmes, including those in the new European Union Member States. Furthermore, the SecIGD2 supports the development and coordination of the necessary competences to meet the Vision 2025 as a part of the platform's Competence Maintenance, Education and Training (CMET) working group.